Azure B as a novel cyanide antidote: Preclinical in-vivo studies - Philippe Haouzi (Toxicology Reports, 2020)
We have determined the effects of azure B (AzB), the main demethylated metabolite of methylene blue (MB), on a model of lethal cyanide intoxication. Our rationale was the following: AzB 1- possesses redox properties very similar to those of MB, which is a potent cyanide antidote, 2- may present a higher intracellular diffusibility than MB, 3- is already present in commercially available solutions of MB, and 4- appears very quickly in the blood after MB administration. AzB could therefore be a member of the phenothiazium chromophore family of interest to treat cyanide intoxication. We found, in spontaneously breathing urethane sedated rats, that AzB mimicked the effects of MB by increasing metabolism, ventilation and cardiac contractility up to 30−40 mg/kg. AzB had a lethal toxicity when the dose of 60 mg/kg was reached. Doses of AzB were therefore chosen in keeping with these data and the doses of MB previously used against cyanide intoxication (4–20 mg/kg) in the rat – doses corresponding to those used in humans to treat methemoglobinemia. KCN, infused at the rate of 0.375 mg/kg/min iv for 13 min, was fatal within 15 min in 100 % of our un-anesthetized rats. AzB at the dose of 4 mg/kg (n = 5) or 10 mg/kg (n = 5) administered 3 min into cyanide infusion allowed 100 % of the animals to survive with no clinical sequelae. The onset of coma was also significantly delayed and no apnea or gasping occurred. At the dose of 20 mg/kg, AzB was much less effective.At 4 mg/kg, the antidotal effects of AzB were significantly better than those produced by MB at the same dose and were not different from the effects produced by 20 mg/kg MB. We conclude that AzB is a potent cyanide antidote at relatively low doses.